Functional and metabolic characteristics of peripheral blood mononuclear phagocytes in patients with different clinical courses of multiple sclerosis - O. M. Koliada; N. I. Vdovichenko; T. I. Kolyada; O. P. Bilozorov (Regulatory Mechanisms in Biosystems, 2020)
Functional and metabolic features of intact and stimulated mononuclear phagocytes were studied in patients with different clinical courses of multiple sclerosis, the study included 66 patients with relapsing-remitting and 32 patients with progressive course of multiple sclerosis. The state of the mononuclear phagocytes was characterized by expression of costimulatory molecules and direction of L-arginine metabolism. Relative quantities of CD80, CD86 and PD-L1 positive monocytes were determined with Phycoerytrin-labeled monoclonal antibodies in immunofluorescence test in peripheral blood and after culture in parallel series with addition of: (a) E.coli lipopolysaccharide (a stimulator of TLR4), (b) a single-stranded RNA – preparation ssRNA40/LyoVec (a stimulator of TLR7/8), (c) IL-4 (an anti-inflammatory interleukin). The formation of NO was determined by the amount of nitrite in the culture supernatants, arginase activity was determined in cell lysates of the monocyte fraction. We showed that functional and phenotypic characteristics of monocytes depend on the clinical course of multiple sclerosis. In patients with progressive course, the relative number of CD86+ cells was significantly higher and PD-L1+ cells significantly lower than in patients with relapsing-remitting course and healthy persons, in patients with relapsing-remitting course the number of PD-L1+ cells was increased. The number of CD80+ cells did not show any significant difference in the investigated groups of patients relative to the control group. In vitro stimulation of peripheral blood monocytes with TLR4/8 produced a significant increase in the number of CD86+ and decrease in the number of PD-L1+ cells in patients with the progressive course. In patients with the relapsing-remitting course LPS produced an increase in number of PD-L1+ cells. We did not find any difference in activity of the arginase pathway of L-arginine metabolism in the intact monocyte fraction of peripheral blood in patients with multiple sclerosis versus the control group, but stimulation with TLR4 agonist of mononuclear cells of patients with progressive course caused significant increased arginase activity versus baseline. At the same time, versus control cells arginase activity in patients with the progressive course decreased after LPS treatment, but trended to increase after TLR7/8 treatment. In patients with the relapsing-remitting course these changes had a similar direction but were less expressed. The results may be considered as an indication of the activation of peripheral blood monocytes and their polarization trend in the M1 direction in patients with the progressive course of multiple sclerosis, these changes could be considered as signs of violation of autoimmune regulatory mechanisms in multiple sclerosis.